The Specific Connexin 43–Inhibiting Peptide Gap26 Improved Alveolar Development of Neonatal Rats With Hyperoxia Exposure - Qing, Cai; Xinyi, Zhao; Xuefei, Yu; Xindong, Xue; Jianhua, Fu (Frontiers in Pharmacology, 2021)
Abstract: Bronchopulmonary dysplasia (BPD) is a common devastating pulmonary complication in preterm infants. Alveolar maldevelopment is the crucial pathological change of BPD, highly associated with oxidative stress-medicated excessive apoptosis. Cellular injury can be propagated and amplified by gap junction (GJ)-mediated intercellular communication. Connexin 43 (Cx43) is the most ubiquitous and critical GJ protein. Gap26 is a specific Cx43 mimic peptide, playing as a Cx43-GJ inhibitor. We hypothesized that Cx43-GJ was involved in alveolar maldevelopment of BPD via amplifying oxidative stress signaling and inducing excessive apoptosis. Neonatal Sprague-Dawley rats were kept in either normoxia (21% O2) or hyperoxia (85% O2) continuously from postnatal day (PN) 1 to 14 in the presence or absence of Gap26. Moreover, RLE-6TN cells (type II alveolar epithelial cells of rats) were cultured in vitro under normoxia (21% O2) or hyperoxia (85% O2). RLE-6TN cells were treated by N-acetyl cysteine (NAC) (a kind of reactive oxygen species (ROS) scavenger) or Gap26. Morphological properties of lung tissue are detected. Markers associated with Cx43 expression, ROS production, the activity of ASK1-JNK/p38 signaling pathway, and apoptotic level are detected in vivo and in vitro, respectively. In vitro, the ability of GJ-mediated intercellular communication was examined by dye-coupling assay. In vitro, our results demonstrated ROS increased Cx43 expression and GJ-mediated intercellular communication; Gap26 treatment decreased ROS production, inhibited ASK1-JNK/p38 signaling, and decreased apoptosis. In vivo, we found that hyperoxia exposure resulted in increased ROS production and Cx43 expression, activated ASK1-JNK/p38 signaling, and induced excessive apoptosis. However, Gap26 treatment reversed these changes, thus improved alveolar development in neonatal rats with hyperoxia exposure. In summary, oxidative stress increased Cx43 expression and Cx43-GJ-mediated intercellular communication. And Cx43-GJ-mediated intercellular communication amplified oxidative stress signaling, inducing excessive apoptosis via ASK1-JNK/p38 signaling pathway. The specific Connexin43 inhibiting peptide Gap26 was a novel therapeutic strategy to improve the alveolar development of BPD.